ANALISIS TEKNIKAL DENGAN MEGGUNAKAN INDIKATOR RELATIVE STRENGTH INDEX (RSI) DAN STOCHASTIC OSCILLATOR DALAM MENENTUKAN SINYAL BELI DAN SINYAL JUAL SAHAM (STUDI PADA SUB-SEKTOR MAKANAN DAN MINUMAN PERIODE 2015-2017) - Kuswardhani, Asti (Jurnal Ilmiah Mahasiswa FEB, 2018)
(English) Investment in fianancial asset especially stock has its own attractiveness for investors because fluctuations in price movements that occur provide opportunities for investors to earn substantial profits, when compared with interest income obtained by customers from the deposit of funds in the bank in the form of deposits or saving products. The purpose of this resource is to know is there any significant differences of buy signal and sell signal before and after using indicator of Relative Strength Index (RSI) and Stochastic Oscillator. This research is an explanatory research do on the company's stock of food and beverage sub-sector period  2015-2017. Statistical analysis used in this research is descriptive statistical analysis, paired sample t test, and wilcoxon test with SPSS 21 calculation tool. Keywords : Technical Analysis, Relative Strength Index (RSI), Stochastic            Oscillator, Buy Signal and Selling Signal.